Risk factors related to the failure of prevention of hepatitis B virus Mother-to-Child transmission in Yunnan, China. Issue 4 (23rd January 2017) - Kang, Wenyu; Li, Qiongfen; Shen, Liping; Zhang, Lifen; Tian, Ziying; Xu, Lin; Qiu, Feng; Wang, Feng
Abstract: Objective: To investigate the relationship between the failure of prevention of hepatitis B virus Mother-to-Child transmission and HBV serological pattern, viral load as well as HBV genotypes. Methods: 2765 pairs of mother-infant matched samples were collected. These pregnant women were HBsAg positive and delivered at hospital from January 1st, 2011 to June 30th, 2011. Of these samples, 26 pairs of sera samples were randomly selected from 114 pairs of samples which failed in the prevention of hepatitis B virus Mother-to-Child transmission. Serological tests, viral load and genotype detection were performed for further analysis. Additionally, the selected subjects were followed and tested again in 2014. Results: HBeAg positive rates were 76.92% and 69.23% in mother group and infant group respectively, showed no statistical difference. The average HBV DNA levels were >2 × 10 5  IU/ml in both mother group and infant group. Genotype analysis revealed that 11 pairs of mother-infant matched samples belonged to C gene type and another 11 pairs were B gene type. Different genotypes were observed in 4 pairs of mother-infant matched samples. Conclusion: HbeAg positive and high HBV DNA level were two major risk factors of HBV mother to child transmission. Additionally, nosocomial infection was another potential way of HBV vertical transmission, especially in remote area of Yunnan province.